2017
DOI: 10.18632/oncotarget.17149
|View full text |Cite
|
Sign up to set email alerts
|

Andrographolide ameliorates d-galactosamine/lipopolysaccharide-induced acute liver injury by activating Nrf2 signaling pathway

Abstract: Andrographolide (ADH), a diterpenoid lactone extracted from Andrographis paniculata, has been found to have anti-inflammatory and anti-oxidative effects. However, its protective effects and mechanisms on liver injury have not been investigated clearly. This study takes an attempt to reveal the protective effects and mechanism of ADH on lipopolysaccharide (LPS) and D-galactosamine (D-GalN)-induced acute liver injury in mice. The mice liver injury model was induced by LPS (60 mg/kg) and D-GalN (800 mg/kg), and A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
33
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(33 citation statements)
references
References 37 publications
(39 reference statements)
0
33
0
Order By: Relevance
“…Andrographolide is the major bioactive component of Andrographis paniculate, which has been traditionally used to treat various of diseases, such as fever, cough, tuberculosis, snake bites, and respiratory or urinary tract infections in Chinese medicine [7][8][9]. Up to now, Andr has also been demonstrated to possess several beneficial properties and therapeutic potential, including anti-cancer, anti-bacterial, anti-inflammation, anti-diabetic, anti-hyperlipidemic, immunomodulation, hepatoprotective, and anti-oxidative effects [10][11][12][13][14][15]. In recent years, some studies have found that Andr inhibits saturated fatty acids induce c-Src aggregating within membrane subdomains and exert anti-atherosclerosis effects by JNK activation [16].…”
Section: Ivyspringmentioning
confidence: 99%
See 1 more Smart Citation
“…Andrographolide is the major bioactive component of Andrographis paniculate, which has been traditionally used to treat various of diseases, such as fever, cough, tuberculosis, snake bites, and respiratory or urinary tract infections in Chinese medicine [7][8][9]. Up to now, Andr has also been demonstrated to possess several beneficial properties and therapeutic potential, including anti-cancer, anti-bacterial, anti-inflammation, anti-diabetic, anti-hyperlipidemic, immunomodulation, hepatoprotective, and anti-oxidative effects [10][11][12][13][14][15]. In recent years, some studies have found that Andr inhibits saturated fatty acids induce c-Src aggregating within membrane subdomains and exert anti-atherosclerosis effects by JNK activation [16].…”
Section: Ivyspringmentioning
confidence: 99%
“…Andr was reported to protect liver cells from H2O2 induced cell death by upregulation of Nrf-2/HO-1 mediated via Adenosine A 2a receptor signaling [19]. Andr ameliorates d-galactosamine/lipopolysaccharide-induced acute liver injury by activating Nrf2 signaling pathway [15]. Furthermore, studies indicated that Andr protected against cigarette smoke-induced oxidative lung injury via augmentation of Nrf2 activity [20].…”
Section: Ivyspringmentioning
confidence: 99%
“…In this study, mRNA expression of HO-1, GR, GCLM, GPx-2, and NQO1 increased by andrographolide treatment. Andrographolide increased Nrf2 and HO-1 proteins in liver of BALB/c mice treated with LPS/D-galactosamine (1 h) followed andrographolide (2.5, 5, or 10 mg/kg) by intraperitoneal for 8 h [6]. Andrographolide increased Nrf2 translocation in liver of C57BL/6 mice orally treated with acetaminophen for 2 weeks and co-treated with andrographolide (20 or 40 mg/kg) every day during an additional 4 weeks [33].…”
Section: In Vivo Studiesmentioning
confidence: 93%
“…Main effects of andrographolide on Nrf2 pathway in vivo, Symbols: " " for an increase, " " for a decrease, and "-" for not communicated. SOD activity (liver, kidney, heart, and red blood cells); CAT activity (heart); GSH peroxidase activity (kidney); GSH reductase (kidney, heart, and red blood cells); GSH S-transferase (liver); GSH protein (heart); antioxidant proteins (SOD1, GST Ya, GST Yb, HO-1, GCLC, and GCLM) (liver, kidney, and heart); mRNA (GCLC, GCLM, GST Ya/Yb, SOD1, and HO-1) (liver and kidney) [25] Wistar rats 0.1 mg/kg, intraperitoneal (6 h) -----HO-1 protein (brains) [85] BALB/c mice 5 or 10 mg/kg, intraperitoneal (1 and 24 h) --(lung) -mRNA (lung) HO-1, GR, GCLM, GPx-2, and NQO1 (mRNA) [96] BALB/c mice LPS/GalN (1 h) followed by andrographolide (2.5, 5, or 10 mg/kg), intraperitoneal (8 h) -(liver) ---HO-1 protein (liver) [6] C57BL/6 mice Acetaminophen (orally) every day for 6 weeks followed by andrographolide (20 or 40 mg/kg, orally) treatment every day at 2 weeks after acetaminophen administration --(liver) --ANDRO reversed the decreased hepatic expression of GCLC, GCLM and HO-1 mRNA expression induced by acetaminophen. Co-treatment with ANDRO (40 mg/kg) NQO1 mRNA [33] C57BL/6 mice Streptozotocin (intraperitoneal injection) for 5 consecutive days followed by andrographolide (1, 10, or 20 mg/kg/day) for 12 weeks by intragastric gavage (heart) ----SOD activity ; MDA and 4-HNE ; Nox2, Nox-4, p47 phox , Nrf2, and HO-1 mRNA [54] Balb/c mice Toluene diisocyanate treatment (dermally and intranasally) for asthma induction with andrographolide treatment (0.1, 0.5, or 1 mg/kg, prophylatic regimen) -(lung) ---HO-1 protein (1 mg/kg, lung) [97] Andrographolide increased Nrf2 protein in lung of Balb/c mice sensitized (dermally and intranasally) with toluene diisocyanate for asthma induction and treated with andrographolide 0.1, 0.5, or 1 mg/kg [97].…”
Section: In Vivo Studiesmentioning
confidence: 99%
See 1 more Smart Citation